Denaturation-enhanced droplet digital PCR for liquid biopsies - Fitarelli-Kiehl, Mariana (Clin Chem, 2018)
BACKGROUND. While interest in droplet-digital PCR technology (ddPCR) for circulating-DNA (cfDNA) analysis is burgeoning, the technology is compromised by sub-sampling errors and the few clinical targets that can be analyzed from limited input DNA. The paucity of starting material acts as a ‘glass ceiling’ in liquid biopsies since, irrespective how sensitive ddPCR techniques are, detection limits cannot be improved past DNA input limitations. Here we show that complete sample denaturation prior to ddPCR approximately doubles the data obtained from a given amount of input DNA. METHODS. We apply denaturation-enhanced ddPCR (dddPCR) using fragmented genomic DNA (gDNA) with defined mutations. We then test dddPCR on cfDNA from volunteers and cancer patients for commonly-used mutations. Genomic-DNA (gDNA) and cfDNA are tested with and without end-repair prior to denaturation and digital-PCR. RESULTS. We demonstrate that by applying complete denaturation of double-stranded DNA prior to ddPCR droplet-formation the number of positive droplets increase. dddPCR using gDNA results to 1.9–2-fold-increase in data-positive droplets, while dddPCR applied on highly-fragmented circulating-DNA results to 1.6–1.7-fold increase. Moreover, end-repair of circulating-DNA before denaturation enables circulating-DNA to display 1.9–2-fold increase in data-positive signals, like gDNA. These data indicate that doubling of data-positive droplets doubles the number of potential ddPCR assays that can be conducted from a given DNA input and improves ddPCR precision for cfDNA mutation-detection. CONCLUSION. Denaturation-enhanced digital-PCR is a simple and useful modification in ddPCR that enables extraction of more information from low-input clinical samples with minor change in protocols. It should be applicable to all ddPCR platforms for mutation detection and, potentially, for gene copy-number analysis in cancer and prenatal-screening.